The intellectual structure of destination image research in tourism (2001-2023): Background, pre-pandemic overview, shifts during COVID-19 and implications for the future - Torres-Pruñonosa, Jose; Araujo Batlle, Alex; De Esteban Curiel, Javier; Díez-Martín, Francisco (Journal of Vacation Marketing, 2023)
We aim to map the intellectual structure of destination image (DI) research and its theoretical development in two longitudinal periods: firstly, from 2001 and before the outbreak of Covid-19 and approval of vaccines (2001–2020); and secondly, during Covid-19 (2021–2023). This is the first article to use co-citation analysis that focuses solely on DI, identifying the main clusters, intellectual turning points, and citation burst papers in this field. Studying bibliometrics pre- and during Covid-19 can help to understand the impact of the pandemic on research output and the shift in research focus. This methodology expands tourism science by recognising the intrinsic nature of DI from an evaluative and relational point of view. Co-citation refers to the cited not the citing papers. The results in the first period show: 1) theoretical background on DI associated with branding from Destination Management Organisations (DMO); 2) the components of DI and their relationship with visitor behaviour; 3) how the Internet and User-Generated Content (UGC) have become the main sources to perceive DI. Whereas, in the second period, two main shifts have been identified: 1) the impact of the pandemic on tourism and perceived travel risk; 2) the emergence of a new approach focusing on the engagement of people with the destination through life experiences. The conclusions could help suppliers, DMOs, and policymakers to understand the components of DI before and during the pandemic, as well as provide valuable insights for the tourism industry to adapt to the new normal.
Keywords: before covid-19; bibliometric; co-citation; destination image; during covid-19; intellectual structure; theory development; Scopus; JCR